2022
DOI: 10.2478/plua-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

Bumblebee pollination activity in a commercial tomato greenhouse during the winter season

Abstract: Bumblebee activity interaction with solar irradiation, solar irradiation and HPS lighting irradiation, the HPS effect of photoperiod, day temperature and hive density were assessed with tomato fruit weights in a commercial tomato glass greenhouse in 2020–2021. Pollination activity was measured by observing ten randomly chosen cv. ‘Beorange’ tomato plants and by counting bumblebee bruised tomato flowers. MANOVA was conducted between factors and bee activity, followed by Pearson’s correlation. A Mann-Whitney U t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(38 reference statements)
1
0
0
Order By: Relevance
“…Various techniques, for example, manual vibrators, the use of a plant growth regulator, and honeybee and bumblebee pollination, have been used to increase the production of tomatoes and other Solanaceae crops [14]. Compared with manual vibration and the use of a plant growth regulator in tomato crops, a higher yield and seed number were observed for bumblebee-pollinated tomatoes [15], which is consistent with the results obtained from our present study, and another more recent study reported the same findings regarding the increases in fruit size and seed numbers using commercially produced bumblebee pollinators in greenhouse conditions [16]. Also, bumblebee represents a better pollinator than honeybee under greenhouse conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Various techniques, for example, manual vibrators, the use of a plant growth regulator, and honeybee and bumblebee pollination, have been used to increase the production of tomatoes and other Solanaceae crops [14]. Compared with manual vibration and the use of a plant growth regulator in tomato crops, a higher yield and seed number were observed for bumblebee-pollinated tomatoes [15], which is consistent with the results obtained from our present study, and another more recent study reported the same findings regarding the increases in fruit size and seed numbers using commercially produced bumblebee pollinators in greenhouse conditions [16]. Also, bumblebee represents a better pollinator than honeybee under greenhouse conditions.…”
Section: Discussionsupporting
confidence: 92%